2003
DOI: 10.1021/jp027139b
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence in Ruthenium(II) Dendrimers

Abstract: We have investigated the electroluminescent properties of polyamidoamine dendrimers containing pendant [Ru(bpy) 3 ] +2 chromophores. Devices were made using indium tin oxide (ITO) and gold electrodes, and they were compared to devices made from [Ru(bpy) 3 ]+2 films. The turn-on time, steady-state current, and electroluminescence efficiency were analyzed in order to provide information about the ionic and electronic carrier mobilities and the degree of self-quenching of luminescence in these materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 48 publications
0
40
0
Order By: Relevance
“…Currently, novel polymeric materials based on iridium(III) complexes are under investigation because of their potential applications in organic light-emitting devices, [19][20][21][22] as well as in biochemical and biomedical areas. [13][14][15] These polymeric iridium(III)-containing materials offer many remarkable advantages, such as high quantum yields and short phosphorescence lifetimes, as well as the ability of color-tuning because of metal-toligand based radiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, novel polymeric materials based on iridium(III) complexes are under investigation because of their potential applications in organic light-emitting devices, [19][20][21][22] as well as in biochemical and biomedical areas. [13][14][15] These polymeric iridium(III)-containing materials offer many remarkable advantages, such as high quantum yields and short phosphorescence lifetimes, as well as the ability of color-tuning because of metal-toligand based radiation.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15] These polymeric iridium(III)-containing materials offer many remarkable advantages, such as high quantum yields and short phosphorescence lifetimes, as well as the ability of color-tuning because of metal-toligand based radiation. [19,20,22] The straightforward synthesis of complex 5 is depicted in Scheme 1. In this procedure a commercially available monomethyl ether of poly(ethylene glycol) (M n ¼ 2 800 g Á mol À1 , M w ¼ 2 940 g Á mol À1 , PDI ¼ 1.05 according to MALDI-TOF MS) was activated with N,N 0 -carbonyldiimidazole (CDI).…”
Section: Resultsmentioning
confidence: 99%
“…[3] These types of functional polymers have found potential applications as precursors for magnetoceramics [4] or electroluminescent materials. [5] Our group has been continuously exploring the use of metal-containing polymers for a variety of opto-electronic devices. The metal complexes incorporated into polymers could play the roles of photosensitizers, charge transport species, and emission sensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results indicated that, in the case of a phenylene-vinylene encapsulated triphenylamine core [89], there is a drastic reduction in mobility from 5.1 × 10 -6 to 5.5 × 10 -9 cm 2 /Vs after changing the generation number from 0 to 3 [89]. The PAMAM decorated [Ru(bpy) 3 ] + 2 dendrimers exhibited similar trend of mobility reductions with increasing generation number [90]. In contrast, iridium core dendrimers with carbazole in each layer [91] exhibited twofold increase in the mobility from (3-6) × 10 -5 cm 2 /Vs for generation 1 to (7.3-12) × 10 -5 cm 2 /Vs for generation 3.…”
Section: Organic Molecules For Device Applicationsmentioning
confidence: 85%